The Relationship Between Emotion Regulation And Academic Stress In Class XII High School Students: Hubungan Antara Regulasi Emosi Dengan Stres Akademik Pada Siswa Kelas XII Sekolah Menengah Atas - Ameliya Anggraini; Widyastuti Widyastuti (Academia Open, 2022)
This study aims to determine whether there is a relationship between emotional regulation and academic stress in class XII students of SMA Insan Cendekia Mandiri Boarding School. The variables in this study are Emotion Regulation as the independent variable and Academic Stress as the dependent variable. The research was conducted at Insan Cendekia Mandiri High School Boarding School. The number of samples is 64 students, using the saturated sampling technique. The hypothesis is that there is a negative relationship between emotional regulation and academic stress in class XII students of SMA Insan Cendekia Mandiri Boarding School. Data analysis using Pearson correlation technique with the help of SPSS 24.0 for windows. The results of the data analysis of this study indicate a correlation coefficient of -0.448** with a significance value of p = 0.000 <0.05, then Ha is accepted with an effective contribution coefficient value of R Square of 20.0%. It is concluded that there is a negative relationship between emotion regulation and academic stress. it means that if emotion regulation is high then academic stress is low. conversely, if emotion regulation is low then academic stress is high.